Improving Students’ Writing Ability In The Procedure Text Using Duolingo Application At 8 Grade Students Of SMP Negeri 5 Pati 2023/2024 - Mareta Damayanti; Maria Yosephin; Siti Lestari (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
Improving Students’ Writing Ability In The Procedure Text Using Duolingo Application At 8 Grade Students Of SMP Negeri 5 Pati. Final Project, English Study Program, Faculty of Language and Arts Education, Universitas PGRI Semarang. Supervisor I Dra. Maria Yosephin, M.Pd, Supervisor II: Dra. Siti Lestari, M.Pd. This study aims to 1) to find out the improvement of students’ writing competence in procedure text before they are taught using the Duolingo application. 2) to find out the improvement of students’ writing competence in procedure text skills after they are taught using the Duolingo application. 3) to explain the significant difference in students’ writing competence in procedure text taught before and after using Duolingo application. In this study, the researcher used quantitative research. An experimental design was applied in carrying out this study. The researcher took two classes as samples: VIII A (experimental group) and VIII B (control group). The experimental group has been given treatment by duolingo application in procedure text. On the other hand, the control group was not assigned treatment at all. The population in this study was class VIII in the academic year 2023/2024. This study indicated that using Duolingo Application in procedure text is an effective technique. The results of the pre-test mean scores in both classes were 66.34 for the experimental group and 66.94 for the control group. In addition, the mean post-test score of experimental group was 84.78, and the control group was 76.66. These findings were calculated using the t-test formula. The t-test > t-table, based on the test results. T-table 5% percentage is 1.670. the computation shows that 6.180 > 1.670. There is a significant difference in students using the Duolingo application in procedure text for students of grade 8 of SMP Negeri 5 Pati. Students are interested and excited when using Duolingo Application in the learning and teaching process with the goal of developing students’ writing skills. Based on the research findings, the researcher concludes that using Duolingo Application in procedure text can help students to develop and improve students writing skills.